2006
DOI: 10.1038/sj.onc.1209387
|View full text |Cite
|
Sign up to set email alerts
|

Loss of one p53 allele results in four-fold reduction of p53 mRNA and protein: a basis for p53 haplo-insufficiency

Abstract: A haploid genotype may be insufficient to support normal wild-type function. Such haplo-insufficiency has recently been documented for numerous tumour suppressor genes. p53 is a crucial tumour suppressor governing DNA repair, cell cycle arrest and apoptosis via its role as a stressresponsive transcription factor. p53 haplo-insufficiency has been observed in vivo with human familial cancer in Li-Fraumeni Syndrome (LFS) and in mouse p53-knockout models of LFS. The increased tumorigenesis associated with loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…Specifically, we mention using Model-1). This confirms that the stage-1 limiting gene is a tumor suppressor gene, and unlike the p53 gene in chromosome 17p (see [33]), there is little or no haploid insufficiency for this gene in cells with genotype 1 . Using models and methods of this paper, one can easily predict future cancer cases for human eye cancer.…”
Section: Discussionsupporting
confidence: 57%
“…Specifically, we mention using Model-1). This confirms that the stage-1 limiting gene is a tumor suppressor gene, and unlike the p53 gene in chromosome 17p (see [33]), there is little or no haploid insufficiency for this gene in cells with genotype 1 . Using models and methods of this paper, one can easily predict future cancer cases for human eye cancer.…”
Section: Discussionsupporting
confidence: 57%
“…seen in mouse models of haplo-insufficency at the locus, 21 hypomorphoic alleles of the negative regulator MDM2, 22,23 and the affect of polymorphisms in the MDM2 promoter in man. A further exciting form of regulation has been suggested by the discovery of p53 isoforms in all vertebrates tested.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the basal levels of p53 protein are important. This is evident in p53 ϩ/Ϫ cells in which the basal expression level of p53 protein is 25% of that in p53 ϩ/ϩ cells (32). Interestingly, this differential is maintained following oncogenic stress, resulting in an attenuated p53 stress response and reduced p53-dependent apoptosis (32).…”
Section: Discussionmentioning
confidence: 91%
“…Previously we demonstrated that the basal levels of p53 protein are critical for the ability of p53 to mount a stress response, with upregulation of target genes such as CDKN1A (p21) and MDM2, and that below a certain concentration threshold p53 protein may be activated in terms of posttranslational modifications but nonetheless be deficient for activating downstream stress response mediators (32). Our discovery that, in the absence of applied stress, SIRT1-⌬2/9 maintains basal p53 protein levels in cells (see above and Fig.…”
Section: Sirt1-⌬2/9 Is Linked With Induction Of P53-dependent Apoptosmentioning
confidence: 99%